Insolvency Forecasting using model Altman Z-Score and Springate Score Analysis - Junaedy, Junaedy (Advances in Management & Financial Reporting, 2023)
Purpose: This study aims to determine the level of bankruptcy risk among coal mining companies listed on the Indonesia Stock Exchange (IDX) using the Altman Z-Score and Springate Score models. Given the critical role of the coal mining industry in Indonesia’s economy, assessing financial stability is essential for stakeholders, investors, and policymakers to anticipate and mitigate financial distress. Research Design and Methodology: This study employs a quantitative approach using discriminant analysis to evaluate corporate financial health. The financial ratios used in the Altman Z-Score model include Working Capital to Total Assets, Retained Assets to Total Assets, Earnings Before Interest and Tax to Total Assets, and Total Equity to Total Liabilities. Meanwhile, the Springate Score model incorporates Working Capital to Total Assets, Earnings Before Interest and Tax to Total Assets, Earnings Before Tax to Current Liabilities, and Sales to Total Assets. Secondary data from annual financial reports in the Indonesian Capital Market Directory form the basis of this study. Findings and Discussion: The findings indicate that financial statements can serve as an effective tool for predicting corporate bankruptcy. The analysis reveals that certain coal mining companies exhibit significant financial distress while others remain financially stable. The results suggest that both Altman Z-Score and Springate Score models are reliable in assessing the financial viability of companies in the coal sector. Implications: This study provides practical insights for financial decision-making, allowing companies to implement preventive measures against financial distress. It also offers guidance for investors and policymakers to enhance risk assessment frameworks and promote economic stability in the mining sector.